Study of Eugenol and Salicylic Acid Interactions in Hybrid Molecule Encapsulated for Enhanced Antioxidant - Endah Setiani Astuti; Warsito, Warsito; Srihardyastutie, Arie (Graduate School, Universitas Brawijaya, 2023)
Drug development continues to be carried out so that drugs can work effectively. Creating a drug formula can be achieved by combining two or more synergistic drug compounds by hybridization, blending, or synthesis. This study reports findings of antioxidant activity using the good DPPH method from the synthesis of eugenol and salicylic acid using the encapsulation technique. The encapsulation technique uses chitosan as a coating material to protect the active ingredients, taking advantage of its unique functional characteristics, including the ability to form bonds with the crosslink agent sodium tripolyphosphate (Na-TPP) at a speed of 13,500 rpm with a pH of 4.2 to optimize the formulation. The encapsulation system produced majority particles measuring 241.0 ± 19.8 nm, with an encapsulation efficiency of 58.29 ± 0.40%. The results of the compound antioxidant test (CS-ES NP) showed better results than pure ES, with an IC50 value of 1.64 ?g/mL. The morphology results after encapsulation showed round and dense particles, indicating that the ES compound was successfully encapsulated. Keywords: encapsulation, antioxidant, eugenyl salicylate, blending